Pengembangan E-Government Inovasi Pelayanan Publik Kegiatan Hibah dan Bantuan Sosial di Dinas Komunikasi dan Informatika Kabupaten Bogor - Khrisna Widhi Dewanto; Nurudin Santoso; Arief Andy Soebroto (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
The service of public innovation is a government effort to serve the community in organizing its government. The service is packaged in the form of electronic government which can be called E-Government. With the existence of electronic-based governance, it is expected to facilitate and overcome some of the existing problems, one of which is a problem regarding the transparency of funds related to grants and social assistance activities carried out in Bogor Regency. Based on various problems that have occurred, this indirectly lies behind the Bogor Regency government to carry out an innovation to improve the management of grants and social assistance. In this study will implement an innovation in the form of a website that is engaged in the field of E-Government related to public innovation services aimed at submitting proposals for proposed activities along with the amount of funds. The method used in this research is using Rapid Application Development. The web will be implemented using the CodeIgniter framework using the PHP and Javascript programming languages. This research resulted in an application that could conduct an examination of the examinations which would later be submitted, the provision of funding recommendations, the regent's approval and monitoring evaluation. The system is specifically used in the scope of Bogor Regency. The existence of this system is expected to help the process of proposing activity proposals related to grant activities and social assistance to be more efficient and effective, transparency of accountability of activities that are clearer and also tracked and the amount of funds given based on recommendations given by the operator and can be done monitoring related to the activities that have been running and the funds used. For functional testing using two methods, namely Whitebox testing and Black Box.